Application of Next-Generation Sequencing for Genetic Diagnosis in Neonatal Intensive Care Units: Results of a Multicenter Study in China - Zhu, Tianwen; Gong, Xiaohui; Bei, Fei; Ma, Li; Chen, Yan; Zhang, Yonghong; Wang, Xia; Sun, Jingjing; Wang, Jian; Qiu, Gang; Sun, Jianhua; Sun, Yu; et al. (Frontiers in Genetics, 2020)
To identify next-generation-sequencing (NGS) clinical usability and to propose a standard diagnostic routine for critically-ill infants, aged less than 100 days and suspected of having a genetically heterogeneous condition, a retrospective study was conducted between Jan.2016-Dec.2018 at neonatal intensive care units (NICUs) of three tertiary hospitals in Shanghai, China. Whole-exome sequencing (WES) or panel sequencing was performed on 307 patients. Trio-WES, trio-panel, proband-WES, and proband-panel diagnostic yields were 39.71% (83/209), 68.75% (22/32), 59.09% (26/44), and 33.33% (4/12), respectively. Definitive molecular diagnoses of 142 infants (46.25%) uncovered 99 disorders; 21 disorders displayed on 44.37% of the diagnosed patients. Genetic etiologies were identified for 61.73% (50/81) of the deceased infants. One in three (29.58%) diagnosed infants exhibited one of the following four clinical traits which had a higher odds of diagnostic rate: integument abnormality (adjusted odds ratio [aOR], 19.7; 95% confidence interval [CI], 2.5-156.3), complex immune-related phenotypes (aOR, 9.2; 95% CI, 1.4-83.5), mixed nervous system phenotypes and congenital anomalies (aOR, 5.0; 95% CI, 1.3-19.1), or mixed metabolism and nervous system phenotypes (aOR, 4.5; 95% CI, 1.0-21.5). Our results demonstrated that NGS was an effective diagnostic tool. Infants exhibiting integument, complex immune-related conditions, metabolism, and nervous signs have higher chances of carrying variants in known disease-causing genes. The number of specific phenotypes could be used as an independent predictor of a positive molecular diagnosis, rather than an isolated abnormality. We developed a molecular diagnostic procedure for the use of NGS for diagnosis in Chinese NICU population based on individual characteristics.